Monte Carlo Cellular Automata Simulation of Receptor Trafficking in Cell Signal Transduction: Tracking Dimer and Oligomer Formation - Rattanakul, Chontita; Lenbury, Yongwimon (Agriculture and Natural Resources, 2015)
A cellular automata (CA) model of the signal transduction pathway mediated by calcium sensing (CaS) receptors was constructed to investigate the effects of different fractions of healthy (functional) and defective receptors. Receptor trafficking was allowed to take place leading to dimerization and oligomerization which exerted a positive impact on the receptor binding affinity. Snapshots of receptor trafficking and distribution over the cell membrane simulated by the CA model were compared with the no-trafficking case.